Analysis Loading Height of HTR (High Temperature Reactor) Core to Obtain Criticlity of Reactor - Evi Setiawati (Chemical Engineering Diponegoro University, 2015)
High temperatur reactor (HTR) attract to be studied due to it has inherent safety characteristics and capabilities to produce energy economically. Design of reactor core in this study is a blend HTR 10 in China with HTR pebble-bed. The reactor has thermal power of 10 MW with inlet and outlet helium temperatures of 250oC and 700oC. HTR design is a cylindrical with helium gas as a coolant and graphite as a moderator. The HTR uses pebble-bed fuel composed a large amount of particles of TRISO in graphite metrics. Kernel radius used to analyse reactor core height in this research is 225 µm with enrichment of 16% in order to achieve critical condition. Reactor criticality is also influenced by the height of active reactor core where pebble-bed fuel is distributed. Calculation of the reactor criticality at any height variations active core is done with MCNP5 modelling techniques. The modelling is done by making the geometry of reactor and pebble-bed which is distributed by using body-centred cubic lattice in the reactor core. From the MCNP5 calculation, the first criticality of HTR can be achieved on the active core height of 150.9012 cm calculated from the bottom active core with criticality value of 1.00312±0.00090. The higher active reactor core is, the more increasing the reactor criticality is. This is occured due to there are many fuel balls of pebble-bed used, so that activity of fission in reactor increases. However, reactor criticality is still in stable condition in each the rise of active core height from critical core height even though reactor reactivity increases 0.01 Δk/k. The minimum of fuel needed to achieve initial criticality (critical core height) is 11,805 pebbles and 8,906 moderators.